EXPLORING THE PSYCHOLOGICAL NEEDS OF THE MAIN CHARACTER IN THE MOVIE GOOD WILL HUNTING - Wimaguna, I Gde Tresnandika; Widiastuti, Ni Made Ayu; Udayana, I Nyoman (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study aims to analyze and identify the fulfillment of basic psychological needs how this fulfillment shapes the types of motivation. The data were taken from the movie Good Will Hunting through the documentation method and note-taking technique. The data analyzed descriptively using qualitative research methods by applying Self-Determination Theory by Ryan and Deci (2017). Informal methods supported by narrative technique were used in presenting the data analyzed. The findings reveal that the fulfillment of the main character basic psychological needs autonomy (asserted through confronting fears and making authentic decisions), competence (realized by reframing challenges as growth opportunities), and relatedness (achieved through bonds of trust and vulnerability with Sean and Skylar) directly shapes his motivational landscape. His motivations transition dynamically from amotivation, characterized by disengagement and self-sabotage when needs are thwarted, through various forms of extrinsic motivation, culminating in intrinsic motivation driven by emotional liberation and self-determination as needs are met. The analysis underscores that psychological need fulfillment is foundational to motivational quality, facilitated by supportive relationships and self-reflection. Keywords: movie, motivation, basic psychological needs, types of motivation